FEASIBILITY STUDY OF BIRU BEACH MANAGEMENT - Farid Ardyansyah; Merin Nurlita Fitra Dwika (Proceeding of The International Conference on Economics and Business, 2022)
The tourism sector has an important role in increasing the economy in each region, therefore the government is given the right and authority to take advantage of the natural availability in the local area. The tourism industry, not only has an impact on regions but can also improve the Indonesian economy because income and the state increase. According to BPWS (Suramadu Tourism Development Agency), the island of Madura has an open opportunity as a tourism area. Madura has several advantages as a tourist destination, namely assuming the socio-cultural conditions of the Madra people, there are tourist objects of natural beauty that are quite interesting, have arts that are still growing and developing in society. Studies on the feasibility analysis of Blue Beach can assist in providing information regarding the feasibility of Blue Beach by analyzing management aspects. By analyzing one of these aspects, the feasibility of Blue Beach can be known and the results of this research will be beneficial to provide relevant information so that in the future the tourist area will be better and more focused and this area can be known more widely and attract local and outside tourists from Madura Island. . In this study, a qualitative research method was used, a descriptive approach.